2022
DOI: 10.1155/2022/1735603
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Coronal Plane Femoral Intertrochanteric Fractures with a Microexternal Fixator Combined with Proximal Femoral Nail Antirotation

Abstract: Objective. To investigate the different efficacy of proximal femoral nail antirotation (PFNA) combined with or without a microexternal fixator in the treatment of coral-plane femoral intertrochanteric fractures. Methods. 120 patients with intertrochanteric coronal fractures who received treatment in four hospitals from February 2020 to February 2021 were retrospectively included in this study. They were divided into control (PFNA alone, n = 60) and combined treatment group (a microexternal fixator + PFNA, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Fracture reduction is completed under direct vision, thereby achieving early stable fixation, shortening the patient's fracture healing time, and significantly reducing the incidence of screw withdrawal or slippage and malunion. The DAA to the hip joint results in minimal trauma, reduces soft tissue damage caused by surgical operations, shortens operation time, and helps reduce the incidence of infection [14,15] . This study indicates that the clinical effect of the DAA to the hip joint in elderly patients with irreducible intertrochanteric fractures is better than that of the direct lateral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture reduction is completed under direct vision, thereby achieving early stable fixation, shortening the patient's fracture healing time, and significantly reducing the incidence of screw withdrawal or slippage and malunion. The DAA to the hip joint results in minimal trauma, reduces soft tissue damage caused by surgical operations, shortens operation time, and helps reduce the incidence of infection [14,15] . This study indicates that the clinical effect of the DAA to the hip joint in elderly patients with irreducible intertrochanteric fractures is better than that of the direct lateral approach.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%